2012
DOI: 10.3109/09638288.2012.720346
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the barriers to accessing therapy services in rural and remote areas

Abstract: Purpose: Throughout the world, people with a disability who live in rural and remote areas experience difficulty accessing a range of community-based services including speech-, physioand occupational therapy. This paper draws on information gathered from carers and adults with a disability living in a rural area in New South Wales (NSW), Australia to determine the extent to which people living in rural areas may receive a person-centred therapy service. Methods: As part of a larger study in rural NSW into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 23 publications
(33 reference statements)
2
92
0
6
Order By: Relevance
“…Solutions of mentoring and outreach services to build local capacity are supported in the literature, along with other strategies such as telehealth [32,45,50,62]. Increasing support through community-based workers has been shown to lower caregiver stress, thus improving family functioning, impacting positively on future outcomes [63].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Solutions of mentoring and outreach services to build local capacity are supported in the literature, along with other strategies such as telehealth [32,45,50,62]. Increasing support through community-based workers has been shown to lower caregiver stress, thus improving family functioning, impacting positively on future outcomes [63].…”
Section: Resultsmentioning
confidence: 97%
“…This can result in people with ABI living in crisis and confusion and receiving very limited assistance [48,49]. In addition to this, disability studies in NSW have also identified that many people with a disability living in rural and remote areas experience difficulties accessing therapy services, with problematic consequences for people [50].…”
Section: Existing Gapsmentioning
confidence: 99%
“…Access to specialist services for people with developmental disabilities is also a big challenge in most rural regions of Australia, particularly in respect to initial diagnosis. There are only a limited number of specialists who provide service(s) outside of metropolitan areas and it is very costly for specialists to visit rural and remote areas [24,25]. There is a lack of choice when it comes to rural service provision, in some cases, there is only one or even no professional representatives in an area, forcing families to travel, sometimes large distances [26].…”
Section: Introductionmentioning
confidence: 99%
“…In regional and remote regions of NSW, people with disabilities and their carers were found 11 to greatly value speech pathology and other allied health services while highlighting the levels of unmet need, long waiting lists, lack of continuity and consistency in services, and difficulties in accessing therapy. The major causes of these difficulties were identified 11 as workforce shortages, and distances travelled by the family or the AHP.…”
Section: Rural and Remote Australiamentioning
confidence: 99%
“…In 2011, NSW had 24 percent fewer AHP positions per head of population in rural and remote areas than the state's average 10 . Rural AHPs in NSW may travel thousands of kilometres in a year 11 , a factor in low retention rates and recruitment difficulties 12,13 . In regional and remote regions of NSW, people with disabilities and their carers were found 11 to greatly value speech pathology and other allied health services while highlighting the levels of unmet need, long waiting lists, lack of continuity and consistency in services, and difficulties in accessing therapy.…”
Section: Rural and Remote Australiamentioning
confidence: 99%